Ar pasistūmėta sovietinėje istoriografijoje po Henryko Lowmianskio „Studijų apie Lietuvos valstybės ir visuomenės 3 genezę" - Gudavičius, Edvardas (Lietuvos istorijos studijos, 1997)
The problematic of the Lithuanian state’s origin has developed under hard conditions. Monographies about King Mindaugas, which had given a right view of events, were issued by J. Latkowski and J. Totoraitis in the years 1892 and 1905 only. In 1931-1932, the earnest work of H. Lowmianski appeared and raised this problematic to the world level at once. However, the situation led to the misunderstanding of this excellent book. The Second World War broke all scientific work, and the severe ideological regimentation of the Soviet occupant power did not let the research on the state’s formation theme proceed. Only in 1959 did a study by the Russian historian V. Pashuto appear in Moscow, which provided limited possibilities for Lithuanian historians to work in this direction. Nevertheless, those possibilities were not well used because the new generation of medievalists in Lithuania was not yet grown enough.